Analisis sedimentológico y estratigráfico secuencial de las Formaciones Vaca Muerta y Quintuco en el área de Chos Malal, Cuenca Neuquina - Kietzmann, Diego Alejandro (2014)
The Vaca Muerta-Quintuco system (early Tithonian - early Valanginian) is a broad shallowingupward sedimentary cycle consisting of dark bituminous shales, marls, limestones, and sandstones, cropping out in the Neuquén Basin, west-central Argentina. This paper analyzes three sections in Chos Malal area, northern Neuquén province. Detailed facies analysis allows to differentiate six facies associations, representing basinal to middle ramp facies of a homoclinal carbonate ramp system (Vaca Muerta Formation), and basinal to shoreface facies of a mixed carbonate/siliciclastic shelf system (Quintuco Formation), prograding westward from the eastern margin of the basin. Two sequence hierarchies are recognized, including five composite depositional sequences and thirteen high-frequency sequences. These results are useful as analogs in nearby areas, since the shelf breaks mapped by Mitchum and Uliana ends perpendicular to the area of study.